2022
DOI: 10.1177/00317217221100001
|View full text |Cite
|
Sign up to set email alerts
|

What does research say about the texts we use in elementary school?

Abstract: Much of the attention given to literacy, of late, has focused on ensuring that students can read, without consideration to what they are given to read. Kristin Conradi Smith & Elfrieda H. Hiebert discuss four general aspects of the texts used in elementary classrooms – text complexity, text type (narrative versus informational), text format (paper versus screen), and diversity of people presented in the text. They review recent research on each of these text characteristics and then make suggestions for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…There are benefits to incorporating expository texts in the classroom read‐aloud repertoire. Reading content‐specific books helps students develop content knowledge (Cervetti et al, 2012; Conradi Smith & Hiebert, 2022). Scholars have found that by combining expository read‐alouds with real‐world experiences, children can deepen their understanding (Cervetti et al, 2012).…”
Section: Why Read Aloud Expository Books?mentioning
confidence: 99%
“…There are benefits to incorporating expository texts in the classroom read‐aloud repertoire. Reading content‐specific books helps students develop content knowledge (Cervetti et al, 2012; Conradi Smith & Hiebert, 2022). Scholars have found that by combining expository read‐alouds with real‐world experiences, children can deepen their understanding (Cervetti et al, 2012).…”
Section: Why Read Aloud Expository Books?mentioning
confidence: 99%
“…This one might seem so obvious that we are apt to forget it, but if we are to pivot from letting the standard or strategy drive the instruction to more text‐focused comprehension instruction, the first consideration should be, “What texts are we using?” Absent from much of the science of reading discussion has been discourse of the very texts we use (Conradi Smith & Hiebert, 2022). The old way might have involved something like this: “I'm teaching inferring, so which book should I use that really helps me teach that?” The teacher then goes online or goes to their librarian and finds a book that allows for some concrete inference examples.…”
Section: Comprehension Instruction Considerationsmentioning
confidence: 99%